2022
DOI: 10.1093/pnasnexus/pgac176
|View full text |Cite
|
Sign up to set email alerts
|

Return to performance following severe ankle, knee, and hip injuries in National Basketball Association players

Abstract: The purpose of this study was to compare basketball performance markers one year prior to initial severe lower extremity injury, including ankle, knee, and hip injuries, to one- and two-years following injury during the regular NBA season. Publicly available data were extracted through a reproducible extraction computed programmed process. Eligible participants were NBA players with at least three seasons played between 2008 and 2019, with a time-loss injury reported during the study period. Basketball perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A pivotal study examining NBA player performance markers before and after severe lower extremity injuries-including ankle, knee, and hip injuries-between 2008 and 2019 provides critical insights. The study found a notable decline in performance levels in less than half of the players within two years post injury, signifying the profound impact such injuries can have on a player's career trajectory [29].…”
Section: Introductionmentioning
confidence: 87%
“…A pivotal study examining NBA player performance markers before and after severe lower extremity injuries-including ankle, knee, and hip injuries-between 2008 and 2019 provides critical insights. The study found a notable decline in performance levels in less than half of the players within two years post injury, signifying the profound impact such injuries can have on a player's career trajectory [29].…”
Section: Introductionmentioning
confidence: 87%
“…Engaging in sports boasts numerous advantages but also leads to injuries. Several parameters, such as age, sex, sport nature (contact or noncontact), and training intensity, govern the susceptibility of athletes to injuries [5,6].…”
Section: Introductionmentioning
confidence: 99%